Distribution of cultural content through exploitation of cryptographic algorithms and hardware identification - Michail, Harris; Louca, Constantinos; Gavrilis, Dimitris; Gregoriades, Andreas; Anastasiou, Lazaros; Ioannides, Marinos (My University, 2014)
An influential effect of IT to museums and other Cultural Content owners organizations is the digitization of collections and in general their content. In this paper, a framework for distribution and commercialization of cultural content is proposed extending an earlier work of the authors. In this work, the framework has been upgraded to include features that protect the cultural content purchased online, to be freely distributed among users through p2p networks or file transfer or copy/paste, etc. The framework utilizes cryptographic algorithms, hash functions, block ciphers and computer’s static and unique parameters/properties. The first are used for continuous hashing and digest matching of the database’s contents for quality assurance. The block ciphers are used to enable on-line selling, through encryption of digital objects. The computer’s static and unique parameters are used to ensure the customer identity and content-distribution legibility. The system’s architecture that implements the above framework is presented and explained. This work illustrates a novel approach that utilize cryptographic and security techniques for secure distribution of Cultural Content.
Keywords: Block ciphers; Cultural content; Digital heritage; e-Commerce; e-Museum; Hardware identification; Hash functions; On-line Selling